2020
DOI: 10.22271/ortho.2020.v6.i3c.2194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of short term complications following use of retrograde intramedullary femoral interlocking nail for fractures of distal femur

Abstract: Background: Supracondylar fractures of femur constitute 6-7% of all femoral fractures. In elderly patients, they are invariably low-energy fractures predisposed by osteoporosis. Aim of this article is to assess the complications of retrograde intramedullary femoral interlocking nail (RIFIN). Materials and methods: The study was conducted at a tertiary health care centre, cases were selected from November 2017 to December 2018. This prospective study was performed on 37 patients with supracondylar femoral fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 9 Various studies have reported many complications following intramedullary nailings like knee stiffness, implant failure, no-union, infection and protruding nails. 10 One of the most common complications identified secondary to intramedullary nailing of the femur was chronic knee pain. 11 , 12 This may significantly hinder the patient’s ability to do his job and other everyday or recreational activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Various studies have reported many complications following intramedullary nailings like knee stiffness, implant failure, no-union, infection and protruding nails. 10 One of the most common complications identified secondary to intramedullary nailing of the femur was chronic knee pain. 11 , 12 This may significantly hinder the patient’s ability to do his job and other everyday or recreational activities.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Its prevalence has been observed to reach 16.1%. 10 Several studies have indicated a significant occurrence of knee pain with estimates ranging from 20% to 86% and even 17% of the patients may experience moderate-to-severe pain years after surgery. 14 , 15 Brewster, 16 in his systematic review, stressed that 40–53% of the individuals who had retrograde intramedullary nailing may experience knee discomfort.…”
Section: Introductionmentioning
confidence: 99%